Nurses’ and patients’ perceptions of caring behaviours: quantitative systematic review of comparative studies - Efstathiou, Georgios; Charalambous, Andreas; Papastavrou, Evridiki (My University, 2011)
Aim. This paper is a report of a systematic review conducted to test the hypothesis that nurses and patients perceive the concept of caring in nursing differently. Background. Caring is viewed as the central focus of nursing. However, despite its fundamental place in clinical practice, researchers and scholars have failed in reaching a common definition. This failure has led to eliciting for nebulous interpretations of the concept often leading to perplexity and opposing views between patients and nurses. Data sources. Extensive search was conducted using MEDLINE, CINAHL and EMBASE between March and May 2009 with no publishing time limit and the keywords ‘care’, ‘caring’, ‘nurse’, ‘nursing’, ‘behavio(u)rs’, ‘patient’, ‘perception’, ‘quantitative’ and ‘comparative’. Review methods. This quantitative systematic review of comparative studies followed the guidance of the Centre for Reviews and Dissemination. A seven-item ‘yes’ or ‘no’ checklist was developed and used for appraising the quality status of the selected literature. Narrative summary technique was used to report outcomes. Results. Evidence of incongruence of perceptions between patients and nurses is mainly supported by the literature. Few studies, however, report aspects of congruence. Conclusion. There is considerable evidence of the assertion that there is no congruence of perceptions between patients and nurses as regards to which behaviours are considered caring and intended caring is not always perceived as such by the patient. Further research is needed, however, to generate more knowledge on the relationship between caring behaviours, patient outcomes and health or nursing costs.
Keywords: Nurse; Patient; Quantitative systematic review; Caring; Perception; Literature review; Behaviours